A pyraclostrobin and difenoconazole suspension and preparation method thereof
By using pine-ester-based grafted cellulose and benzene ring-modified starch in pyrazolestrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostrostro
Patent Information
- Application Number
- CN202411956192.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-28
- Publication Date
- 2025-04-04
AI Technical Summary
Pyrazolestrobin and phenyl ether mecyclazole suspension agents have chemical bond decomposition reactions, agglomeration and sedimentation of the original drug particles in high temperature environments, resulting in the product's thermal storage stability and drug efficacy stability being affected.
Using pine ester-based grafted cellulose and benzene ring modified starch as the main components, a stable and elastic network structure is constructed through the cross-linking of glutaraldehyde to enhance the compatibility and thermal storage stability of the system.
It effectively improves the thermal storage stability and anti-ultraviolet properties of pyrazolestrostrobin and phenyl ether mecyclazole suspension agent, extends the shelf life of the product and the stable performance of the drug effect.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of pesticides, and in particular to a pyraclostrobin and difenoconazole suspension and a preparation method thereof. Background Art
[0002] In the field of agricultural production, effective prevention and control of pests and diseases is a key link in ensuring the yield and quality of crops. Fungicides, as important plant protection products, play an indispensable role in controlling plant diseases. As highly effective and broad-spectrum fungicides, pyraclostrobin and difenoconazole are widely used in the prevention and control of diseases of various crops. They have unique bactericidal mechanisms and can exert significant inhibitory effects on different types of pathogens. Therefore, they are deeply favored by farmers and agricultural practitioners, and the market demand continues to grow.
[0003] However, in the actual formulation development process, many challenges were encountered when compounding pyraclostrobin and difenoconazole to prepare suspension concentrates. Due to the chemical structure characteristics of these two original drugs, their chemical bonds are prone to decomposition reactions in high-temperature environments, resulting in a decrease in the content of active ingredients, weakening the bactericidal power, and frequent agglomeration and sedimentation of the original drug particles during hot storage, which destroyed the uniformity of the suspension system and caused the product to show adverse signs such as stratification and precipitation. This series of hot storage stability issues greatly limits the shelf life, storage conditions and stable performance of the actual efficacy of the product, so it needs to be improved. Summary of the invention
[0004] In order to improve the thermal storage stability of pyraclostrobin and difenoconazole suspensions, the present application provides pyraclostrobin and difenoconazole suspensions and preparation methods thereof.
[0005] The present application provides a pyraclostrobin and difenoconazole suspension and a preparation method thereof using the following technical scheme: In the first aspect, the present application provides a pyraclostrobin and difenoconazole suspension, which adopts the following technical solution: A pyraclostrobin and difenoconazole suspension, wherein the raw materials for preparing the suspension include the following components in parts by weight: 5-10 parts of rosin ester grafted cellulose 3-8 parts of benzene ring modified starch Glutaraldehyde 0.1-0.3 parts Pyraclostrobin TC 10-30 copies Difenoconazole 10-20 parts Emulsifier 6-10 parts Thickener 1-2 parts Preservative 0.9-1.5 parts Make up to 100 parts with water.
[0006] Rosin ester grafted cellulose has a special molecular structure. The active groups on its molecular chain and the unique spatial arrangement enable it to spontaneously entangle and cross-link with each other in the suspension system, thereby building a stable and elastic network structure, providing a basic support framework for the entire system and effectively carrying other components; the introduction of benzene rings into benzene ring-modified starch enhances the regularity of the starch molecular chain and improves its stability in the system. The electron cloud distribution characteristics of the benzene rings generate stronger intermolecular forces between it and the original drug molecules and other additives, greatly enhancing the compatibility of the system. The two work together to The two components work together to stably wrap the original drug; when glutaraldehyde participates in the reaction as a cross-linking agent, its aldehyde group can chemically react with active groups such as hydroxyl groups in the rosin-grafted cellulose and benzene-modified starch molecules to form covalent bonds, thereby improving the overall stability and mechanical strength of the wall material, effectively resisting thermal disturbances, reducing the aggregation and precipitation of the original drug due to heat, and improving the thermal storage stability of the suspension; the synergistic effect of each component can improve the stability of the suspension during storage and use, effectively protect the active ingredients, reduce the impact of environmental factors on the original drug molecules, and thus improve the disease prevention and control effect.
[0007] Preferably, the raw materials for preparing the rosin ester grafted cellulose include maleic rosin and microcrystalline cellulose.
[0008] Maleic rosin is obtained by modifying rosin with maleic anhydride. The unsaturated double bonds and carboxyl groups introduced into its molecular structure are active groups. During the grafting reaction, these active groups react chemically with the hydroxyl groups of microcrystalline cellulose to form strong chemical bonds, thereby promoting the two to build a highly cross-linked network structure. Under thermal storage conditions, the network structure can effectively constrain the movement of molecular chains by virtue of its cross-linking characteristics, reduce the aggregation and sedimentation of the original drug molecules due to thermal motion, and improve the thermal storage stability of the suspension. The unsaturated double bonds in the maleic rosin molecules construct an electronic conjugation system, which can absorb the energy of ultraviolet rays and release the absorbed energy in the form of harmless heat energy through electronic transitions and energy dissipation, thereby avoiding the direct effect of ultraviolet rays on the original drug molecules, improving the stability of the active ingredients in the suspension, and enabling it to continuously and efficiently exert its efficacy.
[0009] Preferably, the mass ratio of maleic rosin to microcrystalline cellulose is (0.4-0.6):1.
[0010] The rosin ester-grafted cellulose prepared according to the above mass ratio has good reactivity and compatibility, and can effectively improve the thermal storage stability and UV resistance of the suspension.
[0011] Preferably, the raw materials for preparing the benzene ring modified starch include acetylated starch and 2-(2-hydroxyphenyl)-4,6-diphenyl-1,3,5-triazine.
[0012] The acetyl group in acetylated starch enhances the hydrophobicity of starch. In the suspension system, it can reduce the effect of moisture on the starch molecular chain, reduce the risk of molecular chain hydrolysis or excessive swelling caused by moisture, and make the starch structure more stable during thermal storage. 2-(2-hydroxyphenyl)-4,6-diphenyl-1,3,5-triazine contains active groups such as benzene ring and hydroxyl group. When preparing benzene ring modified starch, these active groups react chemically with the active sites on the acetylated starch molecules to form stable chemical bonds, further strengthening the overall structure of the starch molecules. The benzene ring structure and its conjugated system convert ultraviolet energy into harmless heat energy and dissipate it through the rearrangement and transition of electrons within the molecule, as well as the transfer and dissipation of energy, effectively preventing ultraviolet rays from destroying the original drug molecules, so that the active ingredients can remain stable under high temperature and strong light irradiation environments, thereby improving the thermal storage stability and anti-ultraviolet performance of the suspension.
[0013] Preferably, the raw materials for preparing the acetylated starch include starch and glutaric anhydride.
[0014] After starch is acetylated with glutaric anhydride, its molecular structure changes and the hydroxyl part is esterified. Acetylation reduces the hydrophilicity of starch, making the starch molecular chain more regular and flexible, and synergistically with the rosin-ester-grafted cellulose, a closer interaction can be formed between molecules, building a stable encapsulation network, enhancing the adsorption and carrying capacity of the original drug, effectively blocking heat transfer during the thermal storage process, reducing the possibility of aggregation and precipitation of the original drug due to thermal movement, and improving thermal storage stability.
[0015] Preferably, the mass ratio of the starch, glutaric anhydride and 2-(2-hydroxyphenyl)-4,6-diphenyl-1,3,5-triazine is 1:0.15:(0.1-0.15).
[0016] The benzene ring modified starch prepared according to the above mass ratio has good compatibility and UV resistance, and can effectively improve the thermal storage stability and UV resistance of the suspension.
[0017] Preferably, the emulsifier includes alkylnaphthalene sulfonate formaldehyde condensate and castor oil polyoxyethylene ether.
[0018] As an anionic surfactant, alkylnaphthalene sulfonate formaldehyde condensate can be dispersed to the interface by electrostatic adsorption, reducing the agglomeration problem during the initial mixing of materials; castor oil polyoxyethylene ether works due to its unique amphiphilic molecular structure. Its hydrophobic group tightly connects the active ingredient and the wall material, while the hydrophilic group extends to the water phase. Through this structural characteristic, a stable hydration film is quickly built in the system; the two work synergistically to increase the compatibility of the active ingredient and the wall material, ensure that the oil phase is evenly dispersed in the water phase, and enable the rosin-modified cellulose and benzene-modified starch to effectively encapsulate the two active ingredient molecules, improve thermal storage stability, and effectively inhibit precipitation caused by particle agglomeration, ensuring that the active ingredients in the suspension can be stably stored so that the efficacy can be fully exerted.
[0019] Preferably, the thickener comprises sodium lignin sulfonate and xanthan gum.
[0020] As an anionic polymer, sodium lignin sulfonate contains a large number of active groups such as sulfonic acid groups on its molecular chain. After being dispersed in water, these groups will be ionized, making the molecular chain carry a negative charge. There is electrostatic repulsion between molecules, which promotes the stretching of the molecular chain and increases the fluidity of the system. Xanthan gum has a unique helical molecular structure. In water, it can form a three-dimensional network structure through interactions such as hydrogen bonds between molecules, thereby increasing the viscosity of the system. When the two are used together as thickeners, the initial fluidity of sodium lignin sulfonate helps to ensure the uniform dispersion of xanthan gum, facilitating its construction of a stable network structure. The high-viscosity network structure formed by xanthan gum limits the excessive stretching of the sodium lignin sulfonate molecular chain. The two mutually restrict and complement each other, effectively regulating the viscosity of the system, avoiding the rapid sedimentation of microcapsules due to gravity, and maintaining good suspension stability of the suspension agent. Under hot storage conditions, the thickening system can resist the problems of intensified molecular thermal motion and thinning of the system caused by increased temperature, ensuring the uniform distribution of active ingredients, thereby maintaining stable efficacy.
[0021] Preferably, the mass ratio of xanthan gum to sodium lignin sulfonate is 1:(0.1-0.3).
[0022] The suspension prepared according to the above mass ratio has good thermal storage stability.
[0023] In a second aspect, the present application provides a method for preparing a suspension concentrate of pyraclostrobin and difenoconazole, using the following technical scheme: A method for preparing a pyraclostrobin and difenoconazole suspension comprises the following steps: The pyraclostrobin technical and the difenoconazole technical are dispersed in ethyl acetate to obtain an oil phase; rosin ester grafted cellulose and benzene ring modified starch are mixed and dispersed in water, an emulsifier and glutaraldehyde are added, and the mixture is stirred to obtain an aqueous phase; the oil phase is added to the aqueous phase, and the mixture is stirred while being added to obtain a mixed phase; the pH value is adjusted to alkaline, and after heating and stirring for reaction, the pH value is adjusted to neutral to obtain a microcapsule suspension, and the microcapsules are obtained after filtering and washing; a thickener is dispersed in water to obtain a thickener solution, the thickener solution and a preservative are added to the microcapsules, the balance is supplemented with water, and the mixture is stirred to obtain a preliminary product, and the preliminary product is ground with a sand mill to obtain a pyraclostrobin and difenoconazole suspension.
[0024] The pyraclostrobin and difenoconazole suspension prepared according to the above steps have good heat storage stability and UV resistance.
[0025] In summary, the present application includes at least one of the following beneficial technical effects: 1. Rosin-ester-grafted cellulose has a special molecular structure. The active groups on its molecular chain and the unique spatial arrangement enable it to spontaneously entangle and cross-link with each other in the suspension system, thereby building a stable and elastic network structure, providing a basic support framework for the entire system and effectively carrying other components; the introduction of benzene rings in benzene-modified starch enhances the regularity of the starch molecular chain and improves its stability in the system. The electron cloud distribution characteristics of the benzene rings generate stronger intermolecular forces between it and the original drug molecules and other additives, greatly enhancing the compatibility of the system. The synergistic effect can stably wrap the original drug; when glutaraldehyde participates in the reaction as a cross-linking agent, its aldehyde group can chemically react with active groups such as hydroxyl groups in the rosin-grafted cellulose and benzene-modified starch molecules to form covalent bonds, thereby improving the overall stability and mechanical strength of the wall material, effectively resisting thermal disturbances, reducing the aggregation and precipitation of the original drug due to heat, and improving the thermal storage stability of the suspension; the synergistic effect of each component can improve the stability of the suspension during storage and use, effectively protect the active ingredients, reduce the impact of environmental factors on the original drug molecules, and thus improve the disease prevention and control effect.
[0026] 2. Maleic rosin is obtained by modifying rosin with maleic anhydride. The unsaturated double bonds and carboxyl groups introduced into its molecular structure are active groups. During the grafting reaction, these active groups react chemically with the hydroxyl groups of microcrystalline cellulose to form strong chemical bonds, thereby promoting the two to build a highly cross-linked network structure. Under thermal storage conditions, the network structure can effectively constrain the movement of molecular chains by virtue of its cross-linking characteristics, reduce the aggregation and sedimentation of the original drug molecules due to thermal motion, and improve the thermal storage stability of the suspension; the unsaturated double bonds in the maleic rosin molecules construct an electronic conjugation system, which can absorb the energy of ultraviolet rays and release the absorbed energy in the form of harmless heat energy through electronic transitions and energy dissipation, thereby avoiding the direct effect of ultraviolet rays on the original drug molecules, improving the stability of the active ingredients in the suspension, and enabling it to continuously and efficiently exert its efficacy.
[0027] 3. The acetyl group in acetylated starch enhances the hydrophobicity of starch. In the suspension system, it can reduce the effect of moisture on the starch molecular chain, reduce the risk of molecular chain hydrolysis or excessive swelling caused by moisture, and make the starch structure more stable during thermal storage; 2-(2-hydroxyphenyl)-4,6-diphenyl-1,3,5-triazine contains active groups such as benzene ring and hydroxyl group. When preparing benzene ring modified starch, these active groups react chemically with the active sites on the acetylated starch molecules to form stable chemical bonds, further strengthening the overall structure of the starch molecules. The benzene ring structure and its conjugated system convert ultraviolet energy into harmless heat energy through the rearrangement and transition of intramolecular electrons and the transfer and dissipation of energy, effectively preventing ultraviolet rays from destroying the original drug molecules, so that the active ingredients can remain stable under high temperature and strong light irradiation environments, thereby improving the thermal storage stability and anti-ultraviolet performance of the suspension. DETAILED DESCRIPTION
[0028] The present application discloses a pyraclostrobin and difenoconazole suspension and a preparation method thereof. The raw materials used in the present application can be obtained from commercially available raw materials unless otherwise specified. The present application is further described in detail in conjunction with the embodiments below: Raw material description: microcrystalline cellulose (CAS No.: 9004-34-6), maleated rosin (CAS No.: 8050-28-0), azobisisobutyronitrile (CAS No.: 78-67-1), starch is corn starch, glutaric anhydride (CAS No.: 108-55-4), 2-(2-hydroxyphenyl)-4,6-diphenyl-1,3,5-triazine (CAS: 3202-86-6), pyraclostrobin technical (CAS No.: 175013-18-0), difenoconazole technical (CAS No.: 119446-68-3), alkylnaphthalene sulfonate formaldehyde condensate model is KG DYWELL-1000 (CAS No.: 9084-06-4), castor oil polyoxyethylene ether (CAS No.: 61791-12-6), sodium lignin sulfonate (CAS No.: 8061-51-6), xanthan gum (CAS No.: 11138-66-2), preservative is bit20 (CAS No.: 2634-33-5).
[0029] Example 1 Preparation of rosin ester grafted cellulose The microcrystalline cellulose is dried at 100°C for 2 hours to obtain dry microcrystalline cellulose; the maleic rosin is ground into fine powder to obtain pretreated maleic rosin; 14.29g of dry microcrystalline cellulose is dispersed in 30mL of N,N-dimethylformamide to obtain a microcrystalline cellulose suspension; 5.71g of pretreated maleic rosin is added to the microcrystalline cellulose suspension, and stirred at a speed of 200rpm for 15min to obtain a mixed suspension; 0.1g of azobisisobutyronitrile is added to the mixed suspension, and the mixture is heated to 80°C under nitrogen protection, stirred at a speed of 500rpm for 6h, and after cooling to below 30°C, a solid product is obtained by filtering, and the solid product is washed with anhydrous ethanol and then dried in vacuo at 80°C to obtain rosin-ester-grafted cellulose.
[0030] Preparation of Benzene Ring Modified Acetylated Starch 16g of starch was dispersed in 50mL of deionized water to obtain starch milk; 1mol / L sodium hydroxide aqueous solution was used to adjust the pH to 9, and the mixture was stirred at 25°C for 20min to obtain alkalized starch milk; 2.4g of glutaric anhydride was added to the alkalized starch milk, the temperature was raised to 40°C, and the mixture was stirred at 500rpm for 4h to obtain an acetylated starch solution; 1.6g of 2-(2-hydroxyphenyl)-4,6-diphenyl-1,3,5-triazine was dissolved in 10mL of N,N-dimethylformamide to obtain a modifier solution; under nitrogen protection, the modifier solution was added to the acetylated starch solution, 0.1g of azobisisobutyronitrile was added, the mixture was stirred at 60°C for 4h, the pH was adjusted to 7 using 1mol / L hydrochloric acid aqueous solution, the mixture was centrifuged, the mixture was washed with deionized water and anhydrous ethanol, and the mixture was vacuum dried at 60°C to obtain a benzene ring modified starch.
[0031] Preparation of pyraclostrobin and difenoconazole suspension 10g of pyraclostrobin and 20g of difenoconazole were dispersed in 10mL of ethyl acetate to obtain an oil phase; 5g of rosin-based grafted cellulose and 8g of benzene ring-modified starch were mixed and dispersed in water, 6g of emulsifier and 0.3g of glutaraldehyde were added, and the mass ratio of alkyl naphthalene sulfonate formaldehyde condensate and castor oil polyoxyethylene ether in the emulsifier was 1:1. The mixture was stirred at a speed of 200rpm for 15min to obtain an aqueous phase. The oil phase was added to the aqueous phase within 1h, and the mixture was stirred at a speed of 1000rpm. After the addition was completed, a mixed phase was obtained, and the system was adjusted with a 1mol / L sodium hydroxide aqueous solution. The pH value was increased to 8, and the reaction was stirred at 400 rpm for 2 hours at 40°C. A 1 mol / L hydrochloric acid aqueous solution was used to adjust the pH to 7 to obtain a microcapsule suspension, which was filtered and washed with deionized water to obtain microcapsules. 1 g of a thickener was dispersed in 10 mL of water, and the mass ratio of xanthan gum to sodium lignin sulfonate in the thickener was 1:0.1 to obtain a thickener solution. The thickener solution and 0.9 g of a preservative were added to the microcapsules, and the mixture was supplemented to 100 g with water. The mixture was stirred at 500 rpm for 30 minutes to obtain a preliminary product. The preliminary product was ground with a sand mill for 15 minutes to obtain a suspension of pyraclostrobin and fenpropimorph.
[0032] Example 2 Preparation of rosin ester grafted cellulose The microcrystalline cellulose is dried at 100°C for 2 hours to obtain dry microcrystalline cellulose; the maleic rosin is ground into fine powder to obtain pretreated maleic rosin; 12.5g of dry microcrystalline cellulose is dispersed in 30mL of N,N-dimethylformamide to obtain a microcrystalline cellulose suspension; 7.5g of pretreated maleic rosin is added to the microcrystalline cellulose suspension, and stirred at a speed of 200rpm for 15min to obtain a mixed suspension; 0.1g of azobisisobutyronitrile is added to the mixed suspension, and the mixture is heated to 80°C under nitrogen protection, stirred at a speed of 500rpm for 6h, and after cooling to below 30°C, a solid product is obtained by filtering, and the solid product is washed with anhydrous ethanol and then vacuum dried at 80°C to obtain rosin-ester-grafted cellulose.
[0033] Preparation of Benzene Ring Modified Acetylated Starch 15.38g of starch was dispersed in 50mL of deionized water to obtain starch milk; 1mol / L sodium hydroxide aqueous solution was used to adjust the pH to 9, and the mixture was stirred at 25°C for 20min to obtain alkalized starch milk; 2.31g of glutaric anhydride was added to the alkalized starch milk, the temperature was raised to 40°C, and the mixture was stirred at 500rpm for 4h to obtain an acetylated starch solution; 2.31g of 2-(2-hydroxyphenyl)-4,6-diphenyl-1,3,5-triazine was dissolved in 10mL of N,N-dimethylformamide to obtain a modifier solution; under nitrogen protection, the modifier solution was added to the acetylated starch solution, 0.1g of azobisisobutyronitrile was added, the mixture was stirred at 60°C for 4h, the pH was adjusted to 7 using 1mol / L hydrochloric acid aqueous solution, the mixture was centrifuged, the mixture was washed with deionized water and anhydrous ethanol, and the mixture was vacuum dried at 60°C to obtain a benzene ring modified starch.
[0034] Preparation of pyraclostrobin and difenoconazole suspension 30g of pyraclostrobin and 10g of difenoconazole were dispersed in 10mL of ethyl acetate to obtain an oil phase; 10g of rosin-based grafted cellulose and 3g of benzene ring-modified starch were mixed and dispersed in water, 10g of emulsifier and 0.1g of glutaraldehyde were added, and the mass ratio of alkylnaphthalene sulfonate formaldehyde condensate and castor oil polyoxyethylene ether in the emulsifier was 1:1, and the mixture was stirred at a speed of 200rpm for 15min to obtain an aqueous phase, and the oil phase was added to the aqueous phase within 1h, and the mixture was stirred at a speed of 1000rpm. After the addition was completed, a mixed phase was obtained, and a 1mol / L sodium hydroxide aqueous solution was used to adjust the phase. The pH value is adjusted to 8, and the reaction is stirred at 400 rpm for 2 hours at 40°C. A 1 mol / L hydrochloric acid aqueous solution is used to adjust the pH to 7 to obtain a microcapsule suspension, which is filtered and washed with deionized water to obtain microcapsules; 2 g of a thickener is dispersed in 10 mL of water, wherein the mass ratio of xanthan gum to sodium lignin sulfonate in the thickener is 1:0.3 to obtain a thickener solution, the thickener solution and 1.5 g of a preservative are added to the microcapsules, and the mixture is supplemented to 100 g with water, and stirred at 500 rpm for 30 minutes to obtain a preliminary product, and the preliminary product is ground with a sand mill for 15 minutes to obtain a pyraclostrobin and difenoconazole suspension.
[0035] Example 3 Preparation of rosin ester grafted cellulose The microcrystalline cellulose is dried at 100°C for 2 hours to obtain dry microcrystalline cellulose; the maleic rosin is ground into fine powder to obtain pretreated maleic rosin; 13.33g of dry microcrystalline cellulose is dispersed in 30mL of N,N-dimethylformamide to obtain a microcrystalline cellulose suspension; 6.67g of pretreated maleic rosin is added to the microcrystalline cellulose suspension, and stirred at a speed of 200rpm for 15min to obtain a mixed suspension; 0.1g of azobisisobutyronitrile is added to the mixed suspension, and the mixture is heated to 80°C under nitrogen protection, stirred at a speed of 500rpm for 6h, and after cooling to below 30°C, a solid product is obtained by filtering, and the solid product is washed with anhydrous ethanol and then dried in vacuo at 80°C to obtain rosin-ester-grafted cellulose.
[0036] Preparation of Benzene Ring Modified Acetylated Starch 15.69g of starch was dispersed in 50mL of deionized water to obtain starch milk; 1mol / L sodium hydroxide aqueous solution was used to adjust the pH to 9, and the mixture was stirred at 25°C for 20min to obtain alkalized starch milk; 2.35g of glutaric anhydride was added to the alkalized starch milk, the temperature was raised to 40°C, and the mixture was stirred at 500rpm for 4h to obtain an acetylated starch solution; 1.96g of 2-(2-hydroxyphenyl)-4,6-diphenyl-1,3,5-triazine was dissolved in 10mL of N,N-dimethylformamide to obtain a modifier solution; under nitrogen protection, the modifier solution was added to the acetylated starch solution, 0.1g of azobisisobutyronitrile was added, the mixture was stirred at 60°C for 4h, the pH was adjusted to 7 using 1mol / L hydrochloric acid aqueous solution, the mixture was centrifuged, the mixture was washed with deionized water and anhydrous ethanol, and the mixture was vacuum dried at 60°C to obtain a benzene ring modified starch.
[0037] Preparation of pyraclostrobin and difenoconazole suspension 20g of pyraclostrobin and 15g of difenoconazole were dispersed in 10mL of ethyl acetate to obtain an oil phase; 7.5g of rosin-based grafted cellulose and 5.5g of benzene ring modified starch were mixed and dispersed in water, 8g of emulsifier and 0.2g of glutaraldehyde were added, the mass ratio of alkyl naphthalene sulfonate formaldehyde condensate and castor oil polyoxyethylene ether in the emulsifier was 1:1, and the mixture was stirred at a speed of 200rpm for 15min to obtain an aqueous phase, and the oil phase was added to the aqueous phase within 1h, and the mixture was stirred at a speed of 1000rpm. After the addition was completed, a mixed phase was obtained, and a 1mol / L sodium hydroxide aqueous solution was used to adjust the phase. The pH value is adjusted to 8, and the reaction is stirred at 400 rpm for 2 hours at 40°C. A 1 mol / L hydrochloric acid aqueous solution is used to adjust the pH to 7 to obtain a microcapsule suspension, which is filtered and washed with deionized water to obtain microcapsules; 1.5 g of a thickener is dispersed in 10 mL of water, wherein the mass ratio of xanthan gum to sodium lignin sulfonate in the thickener is 1:0.2 to obtain a thickener solution, the thickener solution and 1.25 g of a preservative are added to the microcapsules, and the mixture is supplemented to 100 g with water, and stirred at 500 rpm for 30 minutes to obtain a preliminary product, and the preliminary product is ground with a sand mill for 15 minutes to obtain a pyraclostrobin and difenoconazole suspension.
[0038] Example 4 Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that in Example 4, the amount of maleic rosin used is 3.33 g, and the amount of microcrystalline cellulose used is 16.67 g.
[0039] Example 5 Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that in Example 5, the amount of maleic rosin used is 8.89 g, and the amount of microcrystalline cellulose used is 11.11 g.
[0040] Example 6 Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that in Example 6, the amount of starch used is 16.67 g, the amount of glutaric anhydride used is 2.5 g, and the amount of 2-(2-hydroxyphenyl)-4,6-diphenyl-1,3,5-triazine used is 0.83 g.
[0041] Example 7 Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that in Example 7, the amount of starch used is 14.82 g, the amount of glutaric anhydride used is 2.22 g, and the amount of 2-(2-hydroxyphenyl)-4,6-diphenyl-1,3,5-triazine used is 2.96 g.
[0042] Example 8 Example 8 is based on Example 3. The only difference between Example 8 and Example 3 is that glutaric anhydride is not added when preparing the benzene ring modified starch in Example 8.
[0043] Example 9 Example 9 is based on Example 3. The only difference between Example 9 and Example 3 is that in Example 9, no alkylnaphthalenesulfonate formaldehyde condensate is added to the emulsifier.
[0044] Example 10 Example 10 is based on Example 3. The only difference between Example 10 and Example 3 is that in Example 10, castor oil polyoxyethylene ether is not added to the emulsifier.
[0045] Embodiment 11 Example 11 is based on Example 3, and the only difference between Example 11 and Example 3 is that the mass ratio of xanthan gum to sodium lignin sulfonate in Example 11 is 1:0.05.
[0046] Example 12 Example 12 is based on Example 3, and the only difference between Example 12 and Example 3 is that the mass ratio of xanthan gum to sodium lignin sulfonate in Example 12 is 1:0.4.
[0047] Example 13 Example 13 is based on Example 3, and the only difference between Example 13 and Example 3 is that in Example 13, sodium lignin sulfonate is not added to the thickener.
[0048] Comparative Example 1 Comparative Example 1 is based on Example 3, and the only difference between Comparative Example 1 and Example 3 is that the rosin ester-grafted cellulose in Comparative Example 1 is replaced by microcrystalline cellulose.
[0049] Comparative Example 2 Comparative Example 2 is based on Example 3, and the only difference between Comparative Example 2 and Example 3 is that in Comparative Example 2, the benzene ring-modified starch is replaced by starch.
[0050] Performance testing (1) The GB / T 19136-2021 Determination of thermal storage stability of pesticides was selected as the standard. The samples were stored at (54±2)°C for 14 days. The contents of active ingredients in the samples before and after storage were tested respectively. The thermal storage decomposition rate and the suspension rate after thermal storage were calculated. Each sample was tested three times, and the average value was taken after measurement. The results are recorded in Table 1.
[0051] (2) Anti-ultraviolet performance test: The sample was placed in a UV aging test chamber and UV light with a wavelength of 250nm-350nm and an intensity of 0.55W / m 2 , UV aging was carried out for 72 hours, the active ingredient content of the sample before and after aging was tested, and the effective ingredient content decrease rate was calculated. Each sample was tested three times, and the average value was taken after measurement. The results were recorded in Table 1.
[0052] Table 1 Test results of thermal storage stability and UV resistance of suspension Test results Thermal storage decomposition rate (%) Suspension rate after hot storage (%) Decline rate (%) Example 1 1.23 93.6 5.3 Example 2 1.21 93.8 5.1 Example 3 1.18 94.2 5.0 Example 4 1.28 92.7 5.9 Example 5 1.35 92.1 5.6 Example 6 1.32 92.6 5.8 Example 7 1.41 91.8 6.5 Example 8 1.36 92.3 6.1 Example 9 1.36 92.1 5.4 Example 10 1.35 91.9 5.7 Embodiment 11 1.28 91.9 5.6 Example 12 1.30 91.5 5.5 Example 13 1.34 90.1 6.0 Comparative Example 1 1.79 87.3 8.4 Comparative Example 2 1.92 84.6 9.7 As can be seen from Table 1, the hot storage decomposition rate of Examples 1-3 is less than 1.23%, the suspension rate after hot storage is greater than 93.6%, and the decrease rate of the active ingredient content after ultraviolet is less than 5.3%, which shows that the pyraclostrobin and difenoconazole suspension prepared in the present application have good hot storage stability and UV resistance.
[0053] As can be seen from Table 1, the only difference between Examples 4 and 5 and Example 3 is that the mass ratio of maleic rosin to microcrystalline cellulose in Example 4 is 0.2:1, and the mass ratio of maleic rosin to microcrystalline cellulose in Example 5 is 0.8:1. Compared with Example 3, the heat storage stability and antioxidant properties of Examples 4 and 5 are reduced; this is because the mass ratio of maleic rosin to microcrystalline cellulose is destroyed, and too much maleic rosin will lead to excessive cross-linking density of the system, which may cause local overheating during the heat storage process; too little maleic rosin has limited modification effect and limited protection, so that the heat storage stability and UV resistance are reduced.
[0054] As can be seen from Table 1, the only difference between Examples 6, 7, and 8 and Example 3 is that the mass ratio of starch, glutaric anhydride, and 2-(2-hydroxyphenyl)-4,6-diphenyl-1,3,5-triazine in Example 6 is 1:0.15:0.05, the mass ratio of starch, glutaric anhydride, and 2-(2-hydroxyphenyl)-4,6-diphenyl-1,3,5-triazine in Example 7 is 1:0.15:0.2, and glutaric anhydride is not added when preparing the benzene ring modified starch in Example 8. Compared with Example 3, the heat storage stability and UV resistance are reduced; this is because the mass ratio of starch, glutaric anhydride and 2-(2-hydroxyphenyl)-4,6-diphenyl-1,3,5-triazine is not within the optimal range. When the dosage is too large, it will affect the normal movement of the molecular chain, resulting in a decrease in the stability of the system; when the dosage is too small, the modification effect is insufficient and the performance improvement is limited; without adding glutaric anhydride, the stability and regularity of the starch molecules are reduced, and the stability of the encapsulation network is reduced, thereby reducing the heat storage stability and UV resistance.
[0055] As can be seen from Table 1, the only difference between Examples 9 and 10 and Example 3 is that in Example 9, no alkylnaphthalene sulfonate formaldehyde condensate is added to the emulsifier, and in Example 10, no castor oil polyoxyethylene ether is added to the emulsifier. Compared with Example 3, Examples 9 and 10 have reduced heat storage stability and UV resistance. This is because reducing any component in the emulsifier will affect the compatibility of the original drug component and the wall material, thereby affecting the stability of the suspension system, thereby reducing the performance of the suspension.
[0056] As can be seen from Table 1, the only difference between Examples 11, 12, and 13 and Example 3 is that the mass ratio of xanthan gum to sodium lignin sulfonate in Example 11 is 1:0.05, the mass ratio of xanthan gum to sodium lignin sulfonate in Example 12 is 1:0.4, and sodium lignin sulfonate is not added to the thickener in Example 13. Compared with Example 3, the thermal storage stability and UV resistance of Examples 11, 12, and 13 are reduced; this is because the amount of sodium lignin sulfonate is changed, too much or too little sodium lignin sulfonate will affect the interaction between the thickener molecules, affect the viscosity of the system, and thus affect the suspension stability of the suspending agent, and the performance of the suspending agent is affected; lack of sodium lignin sulfonate molecules, lack of regulation of the molecular structure of xanthan gum, reduced dispersibility of the system, reduced stability of the suspending agent, and thus reduced performance.
[0057] As can be seen from Table 1, the only difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, the rosin-based grafted cellulose is replaced by microcrystalline cellulose. Compared with Example 3, the heat storage stability and anti-ultraviolet performance of Comparative Example 1 are reduced. This is because the rosin-based grafted cellulose is replaced by microcrystalline cellulose, the maleic rosin is lacking in modification, the stability of the molecular chain structure is reduced, the electron conjugation system is lacking, the anti-ultraviolet performance is reduced, and thus the heat storage stability and anti-ultraviolet performance are deteriorated.
[0058] As can be seen from Table 1, the only difference between Comparative Example 2 and Example 3 is that the benzene ring modified starch is replaced by starch in Comparative Example 2. Compared with Example 3, the heat storage stability and UV resistance of Comparative Example 2 are reduced; this is because the benzene ring modified starch is replaced by starch, lacking the modification treatment of acetyl and triazine, the stability of starch molecules is reduced, the UV resistance is weakened, and thus the performance of the suspending agent is reduced.
[0059] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A pyraclostrobin and difenoconazole suspension, characterized in that: The raw materials for preparation include the following components in parts by weight: 5-10 parts of rosin-ester grafted cellulose 3-8 parts of benzene ring modified starch Glutaraldehyde 0.1-0.3 parts Pyraclostrobin TC 10-30 copies Difenoconazole 10-20 parts Emulsifier 6-10 parts Thickener 1-2 parts Preservative 0.9-1.5 parts Make up to 100 parts with water.
2. A pyraclostrobin and difenoconazole suspension according to claim 1, characterized in that: The raw materials for preparing the rosin ester-grafted cellulose include maleic rosin and microcrystalline cellulose.
3. A pyraclostrobin and difenoconazole suspension according to claim 2, characterized in that: The mass ratio of maleic rosin to microcrystalline cellulose is (0.4-0.6):
1.
4. A pyraclostrobin and difenoconazole suspension according to claim 1, characterized in that: The raw materials for preparing the benzene ring modified starch include acetylated starch and 2-(2-hydroxyphenyl)-4,6-diphenyl-1,3,5-triazine.
5. A pyraclostrobin and difenoconazole suspension according to claim 4, characterized in that: The raw materials for preparing the acetylated starch include starch and glutaric anhydride.
6. A pyraclostrobin and difenoconazole suspension according to claim 5, characterized in that: The mass ratio of the starch, glutaric anhydride and 2-(2-hydroxyphenyl)-4,6-diphenyl-1,3,5-triazine is 1:0.15:(0.1-0.15).
7. A pyraclostrobin and difenoconazole suspension according to claim 1, characterized in that: The emulsifiers include alkylnaphthalene sulfonate formaldehyde condensates and castor oil polyoxyethylene ether.
8. A pyraclostrobin and difenoconazole suspension according to claim 1, characterized in that: The thickeners include sodium lignin sulfonate and xanthan gum.
9. A pyraclostrobin and difenoconazole suspension according to claim 8, characterized in that: The mass ratio of the xanthan gum to sodium lignin sulfonate is 1:(0.1-0.3).
10. A method for preparing the pyraclostrobin and difenoconazole suspension concentrate as claimed in any one of claims 1 to 9, characterized in that: The steps include: The pyraclostrobin technical and the difenoconazole technical are dispersed in ethyl acetate to obtain an oil phase; the rosin ester grafted cellulose and the benzene ring modified starch are mixed and dispersed in water, an emulsifier and glutaraldehyde are added, and stirred to obtain an aqueous phase; the oil phase is added to the aqueous phase, and stirred while adding to obtain a mixed phase, and the pH is adjusted to alkaline, and after heating and stirring for reaction, the pH is adjusted to neutral to obtain a microcapsule suspension, and after filtering and washing, microcapsules are obtained; The thickener is dispersed in water to obtain a thickener solution, the thickener solution and the preservative are added into the microcapsules, the balance is supplemented with water, and the preliminary product is obtained by stirring, and the preliminary product is ground with a sand mill to obtain a pyraclostrobin and difenoconazole suspension.